Implementasi Sistem Informasi Rujukan Terintegrasi (Sisrute) di Instalasi Gawat Darurat RSUD Dr. Doris Sylvanus Palangka Raya - Hijriah, Restu; Adhani, Rosihan; Illiandri, Oski; Arifin, Syamsul; Nugroho, Adi (Universitas Malahayati, 2025)
ABSTRACT The Ministry of Health of the Republic of Indonesia has established the Integrated Referral Information System (SISRUTE) to regulate the referral process of emergency patients vertically and horizontally. However, the practice of its use still varies greatly in various regions and its implementation is considered not optimal. Analyze the obstacles to implementing SISRUTE in the emergency room of RSUD dr. Doris Sylvanus Palangka Raya as a referral hospital in Central Kalimantan Province from the aspects of Communication, Resources, Disposition and Bureaucratic Structure. This is an qualitative research with the data collection process conducted through interviews with 15 informants selected by purposive sampling and document review. The transmission and consistency of information has been done well from the Health Office to the representatives of each health facility, but there is a lack of clarity of information due to the ignorance of other health facilities when they have difficulty using so they do not fill in SISRUTE.. The number of implementing human resources has been increased but is less active, although sources of information, authority, and supporting facilities are available. Bureaucratic arrangements or recruitment are appropriate, but there are no incentives. SPO is available but has not been updated, and a separate SISRUTE management team has been formed to divide responsibilities. The obstacles to the implementation of SISRUTE in the Emergency Room of Dr. Doris Sylvanus Hospital Palangka Raya are lack of clarity of information, limited number and inactivity of implementing human resources, no incentives, and SPO has not been updated. Keywords: Impementation, SISRUTE, Online Referrals, Emergency Department ABSTRAK Kementerian Kesehatan Republik Indonesia telah menetapkan Sistem Informasi Rujukan Terintegrasi (SISRUTE) untuk mengatur proses rujukan pasien gawat darurat secara vertikal maupun horizontal. Namun, praktik penggunaannya masih sangat bervariasi di berbagai daerah dan implementasinya dinilai belum optimal. Menganalisis kendala implementasi SISRUTE di IGD RSUD dr. Doris Sylvanus Palangka Raya sebagai rumah sakit rujukan di Provinsi Kalimantan Tengah dari aspek Komunikasi, Sumber Daya, Disposisi, dan Struktur Birokrasi. Merupakan penelitian kualitatif dengan proses pengumpulan data dilakukan melalui wawancara 15 orang informan yang dipilih secara purposive sampling dan telaah dokumen. Transmisi dan konsistensi penyampaian informasi telah dilakukan dengan baik dari Dinas Kesehatan ke perwakilan masing-masing Fasyankes, namun terdapat kurangnya kejelasan informasi karena adanya ketidaktahuan Fasyankes lain saat kesulitan menggunakan sehingga tidak mengisi SISRUTE. Jumlah SDM pelaksana telah ditambah namun kurang aktif, meskipun sumber informasi, wewenang, dan fasilitas pendukung telah tersedia. Pengaturan birokrasi atau rekrutmen sesuai, namun belum ada insentif. SPO telah tersedia namun belum diperbaharui, serta telah dibentuk tim pengelola SISRUTE tersendiri untuk membagi tanggung jawab. Kendala implementasi SISRUTE di IGD RSUD dr. Doris Sylvanus Palangka Raya adalah kurangnya kejelasan informasi, keterbatasan jumlah dan kurang aktifnya SDM pelaksana, belum ada insentif, dan SPO belum diperbaharui. Kata Kunci: Implementasi, SISRUTE, Rujukan Online, Instalasi Gawat Darurat